(untitled) (European Journal of Economics, Finance and Business Development, 2024)
The theme "Poverty Alleviation in the World: Challenges and Solutions" explores the multifaceted nature of global poverty and delves into the complexities surrounding its eradication. The challenges outlined in the theme encompass not only economic factors but also systemic issues that perpetuate poverty across generations. The article emphasizes the significance of addressing income inequality, unemployment, education disparities, healthcare access, and social and political instability as integral components of any effective poverty alleviation strategy.